Recommendations for the introduction of metagenomic high-throughput sequencing in clinical virology, part I: Wet lab procedure - López-Labrador F. Xavier; Brown Julianne R.; Fischer Nicole; Harvala Heli; Van Boheemen Sander; Cinek Ondrej; Sayiner Arzu; Madsen Tina Vasehus; Auvinen Eeva; Kufner Verena; Huber Michael; Rodriguez Christophe; et al. (Elsevier, 2022)
Metagenomic high-throughput sequencing (mHTS) is a hypothesis-free, universal pathogen detection technique for determination of the DNA/RNA sequences in a variety of sample types and infectious syndromes. mHTS is still in its early stages of translating into clinical application. To support the development, implementation and standardization of mHTS procedures for virus diagnostics, the European Society for Clinical Virology (ESCV) Network on Next-Generation Sequencing (ENNGS) has been established. The aim of ENNGS is to bring together professionals involved in mHTS for viral diagnostics to share methodologies and experiences, and to develop application recommendations. This manuscript aims to provide practical recommendations for the wet lab procedures necessary for implementation of mHTS for virus diagnostics and to give recommendations for development and validation of laboratory methods, including mHTS quality assurance, control and quality assessment protocols.